"Symbolic philosophy of art in the context of anthropol ogy and intercultural interaction: Russia, China, Europe" - G. G. Kolomiets (Интеллект. Инновации. Инвестиции)
The article is a philosophical and critical reflection that arose after a lecture given to the general public. The author has discovered the anthropological and socio-cultural «roll call» of China, Russia, and Europe in the philosophical hermeneutics of art. The purpose of the study was to show that in intercultural interaction, an important factor is the universal human ability to symbolize, symbolic relationships manifested in art. It is concluded that the symbolic philosophy of art points to the aesthetic unconscious as the dignity of the human mind and is capable of conditioning intercultural interactions based on anthropological universal symbolization, which can simultaneously lead to unification and separation of people in the dialogue of cultures of the modern multipolar world. The author follows an anthroposocioecological approach and an axiological methodology involving value interaction in the system: man-society-life-nature. The introduction reveals concepts related to symbolization and philosophy of art, highlights the «aesthetic unconscious» associated with the philosophical theory of symbolism. The main part presents a brief historical digression into the philosophy and aesthetics of symbolism, the anthropological foundations of the symbolic philosophy of art, and symbolic forms in Chinese, Russian, and European poetic art are considered as examples. Attention is drawn to the fact that the aesthetic, according to Kantian philosophy, indicates an anthropological universal ability to symbolize if symbols and images find a place in art. The symbolic philosophy of art has deep philosophical traditions from antiquity to our time. Characterizing the philosophical, anthropological and socio-cultural foundations of the symbolic philosophy of art, the author gives a reference to the supporters of semantic art and symbolic aesthetics in a more detailed examination of the symbolic philosophy of art in Russian, Chinese, and European poetry. In conclusion, the idea is expressed about the need to expand the work on the study of the symbolic philosophy of art as a factor of intercultural interaction in the dialogue of cultures. Symbolic philosophy, using the example of poetic art, in this article touches on musical symbolization and assumes other types of human activity.